Anemia among antenatal mother in urban Malaysia - Soh, Kim Lam; Mohd Tohit, Eusni Rahayu; Japar, Salimah; Soh, Kim Geok; Ab Rahman, Norhaslinda; Abdul Raman, Rosna (Scientific Research Publishing, 2015)
An understanding of factors influencing haemoglobin (Hb) level among antenatal mothers can help healthcare providers assess, take appropriate action and manage anaemia in this risk group more effectively. A cross-sectional study was conducted in urban areas in Malaysia to determine the Hb levels of antenatal mothers and their association with various socio-economic characteristics. Data for this study were collected from pregnant women during their first antenatal check-up at three selected polyclinics in Malaysia. Anaemia in pregnancy was determined by the Hb level recorded during the first and the last antenatal visits. Determination of Hb was either by a photo calorimetric method or by the Sahliís method. A structured self-administered questionnaire was used to identify the factors influencing Hb level among the antenatal mothers. This study found that 73 out of 217 mothers (33%) were anaemic in that their Hb levels were below 11.00 g/dl. The findings also suggested that Hb levels among the antenatal mothers were influenced by various factors such as education level, occupation, and family income. Anaemia was generally more common among antenatal mothers who had a lower level of education and who were from a background of lower family income.